2010
DOI: 10.1038/oby.2009.369
|View full text |Cite
|
Sign up to set email alerts
|

From “Overweight” to “About Right”: Evidence of a Generational Shift in Body Weight Norms

Abstract: In this article, we describe differences in the self‐perception of weight status in the United States between the two most recent National Health and Nutrition Examination Survey (NHANES) periods (1988–1994 and 1999–2004), and test the hypothesis that secular increases in adult mean BMI, adult obesity, and childhood obesity contributed to changes over time in weight perceptions. We find that the probability of self‐classifying as overweight is significantly lower on average in the more recent survey, for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
184
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(204 citation statements)
references
References 28 publications
16
184
2
2
Order By: Relevance
“…Johnson and colleagues examined self‐perceived overweight between 1999 and 2007 in the UK adults and found that during this period of population weight gain, the percentage of individuals with overweight or obesity underestimating their weight status increased. Burke and colleagues 54 reported conceptually similar findings in the US participants: from 1988 to 2004, a period that was associated with rapid increases in population‐level weight gain in the USA, men and women with overweight or obesity became less likely to identify their weight status as being ‘overweight’. A similar pattern of findings has been reported in longitudinal studies examining weight status misperceptions using other US data, among European adults and in studies that have examined temporal changes in parental underestimation of child overweight status over time 13, 55, 56.…”
Section: Surrounded By Obesity and Failing To See Itmentioning
confidence: 74%
See 3 more Smart Citations
“…Johnson and colleagues examined self‐perceived overweight between 1999 and 2007 in the UK adults and found that during this period of population weight gain, the percentage of individuals with overweight or obesity underestimating their weight status increased. Burke and colleagues 54 reported conceptually similar findings in the US participants: from 1988 to 2004, a period that was associated with rapid increases in population‐level weight gain in the USA, men and women with overweight or obesity became less likely to identify their weight status as being ‘overweight’. A similar pattern of findings has been reported in longitudinal studies examining weight status misperceptions using other US data, among European adults and in studies that have examined temporal changes in parental underestimation of child overweight status over time 13, 55, 56.…”
Section: Surrounded By Obesity and Failing To See Itmentioning
confidence: 74%
“…One prediction of this theory is that under‐detection should have become more common as the obesity epidemic has unfolded. In support of this, a number of longitudinal studies have documented that the tendency for individuals with overweight to fail to identify their adiposity and parental underestimation of child overweight have increased concurrently alongside population obesity prevalence 13, 14, 54, 55, 56. Johnson and colleagues examined self‐perceived overweight between 1999 and 2007 in the UK adults and found that during this period of population weight gain, the percentage of individuals with overweight or obesity underestimating their weight status increased.…”
Section: Surrounded By Obesity and Failing To See Itmentioning
confidence: 95%
See 2 more Smart Citations
“…Possible explanations include aging, as body dissatisfaction tends to decrease with age, 3 or a shift in social norms related to body weight. 4 Still, these are relevant findings as the persistence of high body-weight misperception levels is likely to limit the effectiveness of campaigns aimed at weight reduction. In summary, we found a high bodyweight misperception among overweight and obese Swiss adults but, contrary to Spain, no significant increase during period 1997-2007 was observed.…”
mentioning
confidence: 99%